Improving the nutritional values of sorghum grain using hericium spp. and stropharia rugosoannulata - Julian, Arianne V. (Journal of ISSAAS, 2020)
Sorghum (Sorghum bicolor (L.) Moench) is an important cereal that can be used as a less expensive alternative to corn as animal fodder. Sorghum seeds were aseptically impregnated with the mycelia of variouss Hericium spp. and Stropharia rugosoannulata strains to develop a novel method of enriching the nutritional value of animal feed using mushrooms. The moisture, total fat, crude ash, crude protein and carbohydrate content of sorghum grains varied according to mushrooms species. Generally, fermentation with Hericium spp. increased the crude protein and total carbohydrates of the grains, while S. rugosoannulata strains increased crude ash and protein content. Fermentation with Hericium spp. increased the antioxidant activity of sorghum. These results indicate the potential of using mushroom mycelia as an additive to improve the nutritional value of sotghum grains for use as animal feed.